Oikos/Polis Conflict - Zeenath Kausar (International Institute of Islamic Thought, 1996)
Conflict has been an inescapable phenomenon of Western society, particularly since the sixteenth century. If the era of the medieval West is characterized by the conflict between Pope and Emperor, which eventually gave rise to modem nation-states, the postmodem era may rightly be described as one of conflict between family and state. The postmodem conflict can be traced back to the oikos/polis conflict generated by Western political thought, which originated from Greek misogyny. In the same way the church was overthrown in the conflict in the medieval era, the family is being overthrown in the postmodern era by the neo-Marxist radical school of postmodern feminism, which is also called gender feminism. Quite contrary to gender feminists, contemporary Islamic revivalists find no conflict between the two institutions of family and state. They give due recognition to both institutions and consider them as complementary to one another. This is quite observable in their views and activities in the area of women’s issues, particularly that of women’s political participation. The aim of this paper is to examine the debate on women’s political participation between gender feminists and contemporary Islamic revivalists. The paper shall demonstrate how gender feminists prefer women’s political participation at the cost of deconstructing gender and family. The contemporary Islamic revivalists, however, support and encourage women’s political participation-but not at the expense of family and the distinct identity of woman. The paper is divided into three parts. In the first and second parts, the arguments of gender feminists and contemporary Islamic revivalists on women’s political participation shall be analyzed. The third part shall identify and discuss the differences between them. It is followed by a brief conclusion ...